Influence of the Display Monitor on Observer Performance in Detection of Dental Caries - Farzaneh Kaviani; Firoz Pouralibaba; Esrafil Balaei; Farzad Esmaeili; Atabak Kashefimehr (Tabriz University of Medical Sciences, 2007)
Background and aims. Digital imaging continues to gain acceptance in dentistry and video display used for this becomes important. The aim of this study was to assess the influence of the display monitor on observer performance on caries detection. Materials and methods. Artificial enamel lesions were created in 40 extracted teeth at random using 1/4 and 1/2 round burs. Teeth were mounted in dental stone blocks to simulate a hemi-dentition. Approximate exposures were recorded at 70 kVp using a Planmeca (Planmeca Co, Helsinki, Finland) digital imaging system. Three oral and maxillofacial radiologists rated each image on a five-point scale for the presence or absence of lesion. Radiographic images were viewed on the following monitors: (1) LG Flatron 700p (LG Electronics Co., South Korea); (2) Samsung Magicgreen (Samsung Electronics Corp., South Korea); (3) Hansol 710p (Hansol Electronics Corp., South Korea) and (4) Toshiba satellite laptop (Toshiba Computer Corp., Philippines). Examiners were allowed to magnify and adjust density and contrast of each image at will. Receiver Operating Characteristic (ROC) analysis was performed. Data was subjected to repeated measures analysis of variance and ordinal logistic regression to test for significance between variables and to determine odds ratios. Results. Mean ROC curve areas ranged from 0.8728 for the LG monitor to 0.8395 for the Samsung. Repeated measures analysis of variance showed significant differences between observers (P< 0.0001), lesion size (P< 0.0001), examiner/monitor interaction (P< 0.033) and examiner/block interaction (P< 0.013). However, no significant difference was found between monitors. Conclusion. This study suggests that observer performance is independent of the visual characteristics of the display monitor.